2018
DOI: 10.1186/s12905-018-0540-1
|View full text |Cite
|
Sign up to set email alerts
|

Married women’s autonomy and post-delivery modern contraceptive use in the Democratic Republic of Congo

Abstract: BackgroundAlthough use of modern contraception is considered beneficial in lowering maternal and child mortality rates, the prevalence of contraceptive use remains low in the Democratic Republic of Congo. This study examined modern contraceptive use and its linkage to women’s autonomy.MethodsData were drawn from the 2013–2014 Democratic Republic of Congo Demographic and Health Survey. We selected unsterilized and non-pregnant married women who have given birth in the last three years (N = 6680). Logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
7
33
0
Order By: Relevance
“…Lastly and critical to the success of any health system is service acceptability, which is a function of the fit between provided service and user expectations. While education, age and religion have been identified as important correlates of health care service use, they have also been reported to greatly influence service acceptability (Peters et al, 2008;Negin et al, 2009;Sano et al, 2018a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Lastly and critical to the success of any health system is service acceptability, which is a function of the fit between provided service and user expectations. While education, age and religion have been identified as important correlates of health care service use, they have also been reported to greatly influence service acceptability (Peters et al, 2008;Negin et al, 2009;Sano et al, 2018a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…CCU is common in male-dominated settings where women lack the autonomy to make choices on their health [ 18 ]. Studies have shown a positive association between women empowerment and autonomy and their use of contraceptives [ 19 – 21 ]. Women should be free to decide and choose their preferred FP method even in settings with better male involvement and spousal communication on FP [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown influence of male partners in contraception decisions (Morse, Rowen, Steinauer, Byamugisha, & Kakaire, 2014;M. F. Muanda, Ndongo, Messina, & Bertrand, 2017;Orji, Ojofeitimi, & Olanrewaju, 2007;Sano et al, 2018). The limitations of our study could be addressed in future work by using a welldefined family planning intervention, prospectively following women after the discussion with a nurse, and studying a less restricted study population.…”
Section: Discussionmentioning
confidence: 91%